Uji Aktivitas Antidiabetes Kulit Batang Pulai (Alstonia scholaris) melalui Studi In Silico dan Prediksi Profil Farmakokinetika - Nugroho Wibisono; Yoyon Arif Martino (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Alstonia scholaris is a medicinal plant from the Apocynaceae family. Alstonia scholaris stem bark have some medicinal properties, but their effect on antidiabetics mechanisms is still unclear. Alstonia scholaris stem bark have some active compounds such as Echitamine, Beta Sitosterol, Lupeol, Alpha Amyrin Acetate, and Betulinic Acid. Present study was designed to find out the best active compounds of A. scholaris as a potential therapeutics agent against diabetes mellitus. This study involved the molecular docking of 3D structures of those active compounds into GLUT-1 receptor protein, visualized their result using Biovia Discovery Studio and pharmacokinetics profile prediction analysis using pkCSM web page. The molecular docking result show that Echitamine (-8,7 kcal/mol) have the lower energy compared to glibenclamide (-9,6 kcal/mol). Based on pkCSM web page, Echitamine were have a good pharmacokinetics profile.